Aroma Suap Menyuap Pemilu 2024 Menguat, Bagaimana Hukum Dalam Islam? - Hisny Fajrusalam; Kurniasih Kurniasih; Mariya Ulfa Dwi Shafarani; Nurwaci Nurwaci; Putri Dwi Fachrani (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2023)
Presidential elections are carried out with activities called elections or general elections. Election activities are carried out once every five years by adhering to the principles of direct, public, free, confidential, honest and fair. But in reality, there are unpleasant activities when election activities are about to take place, one of which is bribery. This study aims to describe election activities in Indonesia as well as bribery activities in them and are related to Islamic views. This study uses a literacy study method with a qualitative approach. The results of this study indicate that there are causes, reasons and impacts when someone commits an act of bribery. In the view of Islam, bribery is an activity that is not justified because this activity is an act of consuming wealth incorrectly and vanity. From this case several solutions are needed to reduce bribery in Indonesia.